Synthesis and Characterization of Nano‐Encapsulated Black Pepper Oleoresin using Hydroxypropyl Beta‐Cyclodextrin for Antioxidant and Antimicrobial Applications. Issue 12 (December 2013) - Teixeira, Bruna N.; Ozdemir, Necla; Hill, Laura E.; Gomes, Carmen L.
Abstract: Previous studies have reported antimicrobial and antioxidant activity of black pepper oleoresin which is associated to its phenolic compounds and piperine. The ability of cyclodextrins to form an inclusion complex with a guest molecule could improve black pepper oleoresin application, bioavailability, and stability in foods. Hydroxypropyl beta‐cyclodextrin (HPBCD) inclusion complex with black pepper olereosin were synthesized using the kneading method and characterized for its physico‐chemical properties and its antioxidant and antimicrobial activities. Inclusion complex size was 103.9 ± 7.6 nm and indicated to be a polydisperse system. The entrapment efficiency was 78.3 ± 3.6%, which suggests that other constituents in black pepper oleoresin have higher affinities for HPBCD than piperine (major compound in black pepper oleoresin). Thermograms showed the disappearance of oxidation peaks of black pepper oleoresin, proving complex formation with HPBCD. Phase solubility results indicated 1:1 stoichiometric inclusion complex formation and an increase of black pepper oleoresin aqueous solubility with HPBCD concentration. Nano‐encapsulation with HPBCD did not affect ( P > 0.05) total phenolic content; however, it enhanced ( P < 0.05) black pepper oleoresin antioxidant activity. Black pepper oleoresin and its inclusion complex were analyzed for their antimicrobial activity against Escherichia coli K12 and Salmonella enterica serovar Typhimurium LT2. Both free and encapsulated black pepper oleoresin effectively inhibited bacterial growth within the concentration range tested. Black pepper oleoresin encapsulated in HPBCD was able to inhibit Salmonell a at lower ( P < 0.05) concentrations than its corresponding free extract. Therefore, black pepper oleoresin‐HPBCD nanocapsules could have important applications in the food industry as antimicrobial and antioxidant system.